Haematological variations in visually anaemic sheep naturally infected with Haemonchus contortus in farm conditions at arid Rajasthan - SWARNKAR, C P; SINGH, D (The Indian Journal of Animal Sciences, 2018)
With an objective to reduce use of anthelmintic frequency, targeted selective treatment was implemented for farm flocks in arid Rajasthan. An eye color chart developed by CSWRI, Avikanagar was used for screening the flocks at monthly interval from July to March each year (from 2008 to 2016). All the scorings were done on the same day along with collection of faecal and blood samples from visually anaemic sheep and estimated faecal egg counts (FECs) and erythron parameters, respectively. Data generated were used to establish relationship among haematological estimates and intensity of strongyle infection in visually anaemic sheep. Out of 687 visually anaemic sheep, maximum proportion (54.1%) was recorded in monsoon (Jul-Sep). The frequency distribution exhibited a maximum of 36.3% of visually anaemic sheep with high level (>2001 epg) of strongyle infection. The mean intensity of strongyle infection in visually anaemic sheep varied significantly (P2001 epg group). A significant (P